The Implementation of PERMA Number 3 of 2017 Concerning The Guidelines For Dealing With Women's Cases on Laws As an Effort of Women Empowerment In The Judiciary in Madura - Siti Musawwamah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
Women empowerment in the judiciary institution had actually been sought for since the moment of rule enforcement on reasons for divorce and implementation of (valid) divorce before a court hearing. This policy is an affirmation of legal renewal in the UUP (marriage law) and KHI (Compilation of Islamic Law) as well as an entry point for the law protection on women through the guarantee of legal certainty and opportunity to fight for their rights in divorce decisions, including right of gaining nafkah māḍiyah (past/indebted), nafkah 'iddah, nafkah mut’ah, shared assets, haḍānah (child custody) and childcare costs. The problem relates to the execution of the judiciary decision as it deals with some problems. One of which is the fact that there found no rule regarding with mechanism/method as well as time limit for the implementation, while the divorce pledge would be expired within 6 months after the decree of pledge permission. Accordingly, the Supreme Court’s policy to issue PERMA number 3 of 2017 concerning the guidelines for adjudicating women's cases in law shows its significance. Using a qualitative research design, this paper aimed at describing the implementation of PERMA number 3 of 2017 in religious courts in Madura, identifying constraints in its implementation, and explaining in detail the solutions to overcome the constraints. The results of this study are expected to be beneficial as an attempt to empower women by removing all barriers they cope with. Furthermore, it also enables them to gain access on justice without any discrimination in the justice system particularly in the religious court system at all levels, namely the first level, appeal, and cassation.